Reliability and Physiological Interpretation of Pulmonary Gas Exchange by "Circulatory Equivalents" in Chronic Heart Failure. Issue 7 (27th March 2018) - Tan, Chunting; Rossiter, Harry B.; Porszasz, Janos; Bowen, T. Scott; Witte, Klaus K.; Stringer, William W.; Casaburi, Richard; Hansen, James E.
Abstract : Background: Peak ratios of pulmonary gas‐exchange to ventilation during exercise ( V ˙ O 2 / V ˙ E and V ˙ CO 2 / V ˙ E, termed "circulatory equivalents") are sensitive to heart failure (HF) severity, likely reflecting low and/or poorly distributed pulmonary perfusion. We tested whether peak V ˙ O 2 / V ˙ E and V ˙ CO 2 / V ˙ E would: (1) distinguish HF patients from controls; (2) be independent of incremental exercise protocol; and (3) correlate with lactate threshold (LT) and ventilatory compensation point (VCP), respectively. Methods and Results: Twenty‐four HF patients (61±11 years) with reduced ejection fraction (31±8%) and 11 controls (63±7 years) performed ramp‐incremental cycle ergometry. Eighteen HF patients also performed slow (5±1 W/min), medium (9±4 W/min), and fast (19±6 W/min) ramps. Peak V ˙ O 2 / V ˙ E and V ˙ CO 2 / V ˙ E from X‐Y plot, and LT and VCP from 9‐panel plot, were determined by 2 independent, blinded, assessors. Peak V ˙ O 2 / V ˙ E (31.2±4.4 versus 41.8±4.8 mL/L; P <0.0001) and V ˙ CO 2 / V ˙ E (29.3±3.0 versus 36.9±4.0 mL/L; P <0.0001) were lower in HF than controls. Within individuals, there was no difference across 3 ramp rates in peak V ˙ O 2 / V ˙ E ( P =0.62) or V ˙ CO 2 / V ˙ E ( P =0.97). Coefficient of variation (CV) in peak V ˙ O 2 / V ˙ E was lower than for LT (5.1±2.1% versus 8.2±3.7%; P =0.014), and coefficient of variation in peak V ˙ CO 2 / V ˙ E was lower than for VCP (3.3±1.8% versus 8.7±4.2%; P <0.001). In all participants, peak V ˙ O 2 / V ˙ E was correlated with, but occurred earlier than, LT ( r 2 =0.94; mean bias, −0.11 L/min), and peak V ˙ CO 2 / V ˙ E was correlated with, but occurred earlier than, VCP ( r 2 =0.98; mean bias −0.08 L/min). Conclusions: Peak circulatory equivalents during exercise are strongly associated with (but not identical to) LT and VCP. Peak circulatory equivalents are reliable, objective, effort‐independent indices of gas‐exchange abnormality in HF.